Adaptive e-Learning: Emerging Digital Tools for Teaching Parasitology. Issue 4 (April 2019) - Pfeiffer, Caitlin N.; Jabbar, Abdul
Abstract : Adaptive learning activities can respond to a learner's needs in real time, facilitating the development of higher-level skills including bringing together knowledge from different disciplines to solve real-world problems. Here we discuss the use of online adaptive learning activities designed to help veterinary students apply their knowledge to work through parasite case studies.